HUBUNGAN POSTUR DALAM PATIENT HANDLING DENGAN KELUHAN NYERI LEHER (NECK PAIN) PADA PERAWAT RSUD DR. ISKAK TULUNGAGUNG - Hayyun Naha Arifah; Daru Lestyanto; Baju Widjasena (Jurnal Kesehatan Masyarakat, 2019)
Abstract : Neck pain is discomfort feeling which often felt by workers with tense and burning sensations in the area of the neck due to static and repetitive work activities. Nurses carried out risk activities for ergonomics such as strange work postures with repetitive movements and lifting weights. These activities disrupted the health of workers, especially in the musculoskeletal area. The purpose of this study determined the relationship between work posture on the activities of patients handling complaints of neck pain in a central surgical installation nurse. The type of research used quantitative, cross-sectional study. The populations in this study were 40 people with 32 nurses as a sample, the sampling techniques used purposive sampling. The instrument in this study used a nordic body map questionnaire to find out perceived sensations and posture observations using BRIEF survey sheets to observe the risk of nurse's posture. The statistical analysis used the chi-square test. The results showed there was no relationship between the variable posture of lift (p-value 0.198), repositioning (p-value 0.446) and transfer (p-value 0.581). However, there is a relationship between the working period with neck pain (p-value 0.024). The present study enhances our understanding of the influence of safe work posture and appropriate stretching methods. The further socialization is needed by the institute collaborated to physiotherapists in order to prevent neck pain